Studi Eksegesis Terhadap Kolose 2:3 Tentang Ungkapan “Sebab Di Dalam Dialah Tersembunyi Segala Harta Hikmat Dan Pengetahuan” - Hulu, Licin Cermei (Views : Jurnal Teologi dan Biblika, 2024)
Abstract: Colossians 2:3 by examining the historical, literary context, as well as translating and evaluating the text from the original language. The Epistle to the Colossians, believed to have been written by Paul during his first imprisonment in Rome, aims to counter heresies and affirm the supremacy of Christ. In the literary context, Colossians 2:3 highlights that all wisdom and hidden knowledge are in Christ. Analysis of the Greek text shows that the word ἀπόκρυφοι means “hidden,” which is consistent with the New Living Translation (NLT) translation. The analysis of the Greek text shows that the word ἀπόκρυφοι means “hidden,” which is consistent with the New Living Translation (TB) and the Private Translation (TP), while the BIMK Translation renders the word as “uncovered,” which is not entirely appropriate. Word and grammatical analysis show that Christ is the ultimate source of all wisdom and knowledge. Interpretive help confirms that Christ is the center of God's previously hidden mysteries. The exegetical conclusion underlines that in Christ there is all the wisdom and knowledge necessary for a life in accordance with God's will. The relevance for today includes the importance of Christ as the ultimate source of knowledge and wisdom and the direction of a meaningful life in relationship with Him.